Impacts of Land Use on GHG Emissions and Landscape Structure in Monte Carmelo, Minas Gerais (Revista Espinhaço, 2026)
The conservation of natural ecosystems stands as one of the major challenges of this century. Approaches that integrate land use and land cover dynamics, as well as landscape structure and composition, are essential to reconcile agricultural expansion, mitigation of greenhouse gas (GHG) emissions, and the protection of fragile ecosystems, in pursuit of a bioeconomy. This study investigated how changes in land use and cover have affected landscape structure and GHG emissions over approximately four decades in Monte Carmelo (Minas Gerais), an agricultural municipality in the Triângulo Mineiro and Alto Paranaíba region. Data from the MapBiomas project, landscape ecology metrics, and GHG emissions from the SEEG system were used to analyze temporal dynamics and estimate annual emissions. The results revealed a reduction in forest formations (-5.66%) and savanna formations (-52.72%), accompanied by increased fragmentation. Coffee cultivation, soybean farming, silviculture, and other temporary crops expanded primarily over former pasturelands. GHG emissions increased by 31.25%, driven mainly by land use changes and agricultural activities. Landscape metrics indicated increased fragmentation and simplification of vegetation patches. These changes pose significant challenges to biodiversity conservation and climate change mitigation, highlighting the urgent need for local policies and sustainable management practices supported by geospatial data and territorial intelligence.
Keywords: Landscape Ecology; Climate Change; GEE; Forest Fragmentation